2020
DOI: 10.5195/ijt.2020.6337
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Satisfaction with a Video Telehealth Home Safety Evaluation for Dementia

Abstract: Family caregivers are vital to telehealth-delivered dementia care. The objective of this mixed methods descriptive study conducted in the VA Bedford Healthcare System was to examine caregiver satisfaction with a video telehealth dementia home safety occupational therapy evaluation. Ten caregivers of Veterans with dementia participated. Ratings of caregiver satisfaction, measured by nine Likert scale items including ability to see and hear, were examined in relation to person and visit-related contextual factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Expectations that already-burdened caregivers, whether possessing high or low proficiency in information and communication technology (ICT), master a new platform may be impractical 121 ; for it is often incommensurate with patient-monitoring responsibilities. 122 In absence of any thorough investigation, high attrition is a persistent issue in internet-facilitated technology intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…Expectations that already-burdened caregivers, whether possessing high or low proficiency in information and communication technology (ICT), master a new platform may be impractical 121 ; for it is often incommensurate with patient-monitoring responsibilities. 122 In absence of any thorough investigation, high attrition is a persistent issue in internet-facilitated technology intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, for some years now, some isolated strategies have been employed that have proven the effectiveness of education programs in dementia, involving the use of printed support material at psychoeducational meetings, later delivered to caregivers or sent by email to those unable to attend face-to-face support meetings ( 19 , 20 ). These studies have shown that patients and caregivers monitored in specialized services benefit from counseling measures and support groups focused on individualized needs, conferring numerous benefits in terms of both functional and behavioral aspects of patients with dementia, alleviating the burden of caregivers ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, for some years now, some isolated strategies have been employed that have proven the effectiveness of education programs in dementia, involving the use of printed support material at psychoeducational meetings, later delivered to caregivers or sent by email to those unable to attend faceto-face support meetings (19,20). These studies have shown that patients and caregivers monitored in specialized services benefit from counseling measures and support groups focused on individualized needs, conferring numerous benefits in terms of both functional and behavioral aspects of patients with dementia, alleviating the burden of caregivers (21,22). These support materials, such as management and educational manuals that focus on information inherent to health promotion and disease prevention, are very useful in the primary healthcare network, helping both professionals and caregivers in the appropriate management of dementia, and their content can be delivered in person or remotely.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for stroke, unlike telephone visits, video visits allow for assessment of stroke-related deficits through remote physical and neurologic examinations, facilitate interactions with caregivers (outpatient care), and allow for visualization of the home environment. 11 Understanding patient characteristics in relation to telemedicine visits among stroke survivors may help identify barriers and facilitators of telemedicine implementation into routine stroke practice during and after the pandemic. In this study, we sought to evaluate relationships between sociodemographic characteristics and access to telemedicine (video vs telephonic) for outpatient care among patients presenting to stroke clinics associated with 3 different comprehensive stroke centers across the United States during the early time of the pandemic.…”
mentioning
confidence: 99%